Accounting as practice - Major, M. J. M. F.; Clegg, S. (Sociedade, Contabilidade e Gestão, 2019)
In this paper we seek to debate some of the problems affecting positivist accounting research, and how the adoption of organizational theory grounded on qualitative methods can fruitfully contribute to advance research in the area. To this end we draw on research we have previously conducted in Portuguese public hospitals to discuss how the incorporation of power issues, institutional entrepreneurship, hybridization, institutional logics and institutional work in accounting studies fosters in-depth explanations of accounting practice.